Implementing Distributed TDMA Using Relative Distance in Vehicular Networks - Deng, Yafeng; Kim, Dohyung; Li, Zhetao; Choi, Young June (IEEE Transactions on Vehicular Technology, 2020)
With the advent of self-driving cars, vehicular networking is gaining greater attention and the subject of extensive research. It is important to implement a more efficient and secure transportation system by enabling communication among objects on the road. Specifically, safety applications should be delivered in a reliable manner within a limited time period. Several time division multiple access (TDMA) protocols have been proposed to realize this. However, most of the existing research have proposed slot management approaches by taking into account the static topology; they have not sufficiently discussed research on 'merging collision' arising from overlapping two or more collision domains due to vehicle mobility. In this study, we examine the effect of merging collision in terms of packet delivery ratio, overhead, and inter-basic safety message (inter-BSM) delay.11Delay between BSMs received in succession. To mitigate the effect of merging collision, we also propose a lightweight distributed TDMA protocol, where the order of vehicles on the road and their relative distances are exploited to determine the dedicated slot. The collision is further resolved using in-band signaling from the surrounding vehicles. Simulation studies show that the proposed scheme improves the performance of the packet delivery ratio (PDR) 10% more than the comparative protocol, and consequently achieves 97% and 95% PDRs, in highway and urban environment, respectively. Furthermore, the overhead and inter-BSM delay are substantially reduced.
Keywords: Packet delivery ratio; Safety applications; Simulation studies; Time division multiple accesses (TDMA); Transportation system; Urban environments; Vehicular networkings; Vehicular networks; access collision; merging collision; time division multiple access; Vehicular networking